EFEKTIVITAS MODEL DIRECT INSTRUCTION BERBASIS AUDIOVISUAL TERHADAP KEMAMPUAN SENAM LANTAI ROLL BELAKANG PADA SISWA SMPIT HARAPAN UMAT KARAWANG - Hambali, Rifki Yasa; Sumarno, Ardawi; Dermawan, Dikdik Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effectiveness of the audiovisual-based Direct Instruction model on students’ backward roll ability in grade VII students of SMPIT Harapan Umat Karawang. This research used a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The population of this study consisted of all seventh-grade students of SMPIT Harapan Umat Karawang, while the sample was selected using cluster random sampling technique. The experimental group received treatment using the audiovisual-based Direct Instruction model, while the control group received conventional learning. Data were collected through backward roll skill tests consisting of initial position, movement execution, and final position assessment aspects. The results showed that the application of the audiovisual-based Direct Instruction model improved students’ backward roll skills significantly. The learning model provided clear instructions, structured practice stages, and visual demonstrations that helped students understand movement techniques more effectively. Therefore, the audiovisual-based Direct Instruction model can be used as an effective learning alternative in physical education, especially in floor gymnastics learning.